2018
DOI: 10.1111/eci.12939
|View full text |Cite
|
Sign up to set email alerts
|

Rac‐GTPases and Rac‐GEFs in neutrophil adhesion, migration and recruitment

Abstract: Rac-GTPases and their Rac-GEF activators play important roles in the recruitment and host defence functions of neutrophils. These proteins control the activation of adhesion molecules and the cytoskeletal dynamics that enable the adhesion, migration and tissue recruitment of neutrophils. They also regulate the effector functions that allow neutrophils to kill bacterial and fungal pathogens, and to clear debris. This review focuses on the roles of Rac-GTPases and Rac-GEFs in neutrophil adhesion, migration and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 69 publications
(176 reference statements)
1
39
0
1
Order By: Relevance
“…Other than CXCL16, IL-8 was another increased chemokine from HMGB1-treated keratinocytes; this result is consistent with the findings reported by Dejean et al (2012). IL-8 is known to induce the chemotaxis for neutrophils; however, the migration of neutrophils depends not only on the chemotactic function of IL-8 but also on the polarity of neutrophils, which is mediated by Rho GTPases (Pantarelli and Welch, 2018). Recently, some studies have found that 8-hydroxydeoxyguanosine, an oxidative stresseinduced DNA product that is elevated in vitiligo (Vaseghi et al, 2017;Wei et al, 2013), could inhibit the function of Rho GTPases (Park et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Other than CXCL16, IL-8 was another increased chemokine from HMGB1-treated keratinocytes; this result is consistent with the findings reported by Dejean et al (2012). IL-8 is known to induce the chemotaxis for neutrophils; however, the migration of neutrophils depends not only on the chemotactic function of IL-8 but also on the polarity of neutrophils, which is mediated by Rho GTPases (Pantarelli and Welch, 2018). Recently, some studies have found that 8-hydroxydeoxyguanosine, an oxidative stresseinduced DNA product that is elevated in vitiligo (Vaseghi et al, 2017;Wei et al, 2013), could inhibit the function of Rho GTPases (Park et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…AP-1 is also a transcription factor and regulates differentiation, proliferation and apoptosis of the cell [43]. Chemokine-triggered β2 integrin activation can transduce signaling over small GTPases, Rap [27] and/or Rho (Ras homolog gene) [39], Rac-1 (Ras-related C3 botulinum toxin substrate 1) [44], Cdc42 (Cell division control protein 42 homolog) [45], according Rho-GEF such as, CALDAG-GEF [46], DOCK2 (Dedicator of cytokinesis 2) [47], VAV1 (Vav Guanine Nucleotide Exchange Factor 1) [48], kinases, including STK4 (Serine/threonine-protein kinase 4) and SKAP55 (Src kinase-associated phosphoprotein 5) [49], and other signaling proteins like PLD1 (Phospholipase D1) [50] and adaptor proteins as ADAP (Adhesion and degranulation-promoting adaptor protein) [49] and PIP5K1C (Phosphatidylinositol-4-Phosphate 5-Kinase Type 1 Gamma) [51,52]. Altogether, inside-out signaling induces a conformational change of the β2 integrin, leading to a high affinity open state, which results in strong binding of all ligands [53].…”
Section: Activation Of β2 Integrinsmentioning
confidence: 99%
“…Small GTP-binding proteins, also denoted small G proteins, are 20-40 kDa GTPases that participate in many signaling pathways controlling a plethora of cellular functions (reviewed in [164][165][166]). Interestingly, a protein denoted Trio has two guanine nucleotide-exchange factor (GEF) domains, one specific for Rac and the other for Rho, and a protein kinase domain similar to the one in CaMK.…”
Section: Cam-regulated Small G Proteinsmentioning
confidence: 99%